Lignin: Characterization of a Multifaceted Crop Component - Michael Frei (The Scientific World Journal)
Lignin is a plant component with important implications for various agricultural disciplines. It confers rigidity to cell walls, and is therefore associated with tolerance to abiotic and biotic stresses and the mechanical stability of plants. In animal nutrition, lignin is considered an antinutritive component of forages as it cannot be readily fermented by rumen microbes. In terms of energy yield from biomass, the role of lignin depends on the conversion process. It contains more gross energy than other cell wall components and therefore confers enhanced heat value in thermochemical processes such as direct combustion. Conversely, it negatively affects biological energy conversion processes such as bioethanol or biogas production, as it inhibits microbial fermentation of the cell wall. Lignin from crop residues plays an important role in the soil organic carbon cycling, as it constitutes a recalcitrant carbon pool affecting nutrient mineralization and carbon sequestration. Due to the significance of lignin in several agricultural disciplines, the modification of lignin content and composition by breeding is becoming increasingly important. Both mapping of quantitative trait loci and transgenic approaches have been adopted to modify lignin in crops. However, breeding goals must be defined considering the conflicting role of lignin in different agricultural disciplines.